BASIC MOTOR ABILITIES AND SITUATIONAL MOTOR EFFICIENCY WITH YOUNG HANDBALL PLAYERS FROM MONTENEGRO - QUANTITATIVE APPROACH - Aldijana Muratović; Georgi Georgiev (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The research was conducted on 100 young handball players aged from 14 to15, from Montenegro. They were divided into two groups of 50 students each due to the regions they belong to (continental and Mediterranean). They were tested with 26 tests, 21 of which are related to basic motor abilities, and 5 are for estimating situational motor efficiency. The aim of the research is to compare the basic motor and situational motor abilities between the handball players from the two regions. After processing the data by t-test, analysis of variance (ANOVA), and multivariate analysis of variance (MANOVA), the drawn conclusion is that, within the treated space of basic motorics and situational motorics, the handball players from the continental region scored better results than those from Mediterranean region.